Dissolvable Trimolybdate Nanowires as Ag Carriers for High-Efficiency Antimicrobial Applications. (15th February 2012) - Xue, Jiongwei; Ye, Jianwen; Jiang, Yujie; Chen, Mo; Pan, Huayong; Xu, Shengyong; Wang, Wei; Tang, Jie
Abstract : Elimination of bacteria and other microbes effectively is important to our daily life and a variety of medical applications. Here, we introduce a new kind of trimolybdate nanowires, namely Ag 2 − x ( NH 4 ) x Mo 3 O 10 ⋅ 3 H 2 O, that carry a large amount of Ag atoms in the lattice and Ag-rich nanoparticles on the surface. These nanowires can eliminate bacteria of E. coli, Staphylococcus aureus, and unknown microbes in raw natural water with high efficiency. For example, they can inactivate more than 98% of E. coli with a nanowire concentration of only 5 ppm in the solution. The excellent sterilization performance is attributed to the combined effects of Ag ions, Mo ions, and Ag-rich nanoparticles of the Ag 2 − x ( NH 4 ) x Mo 3 O 10 ⋅ 3 H 2 O nanowires. These nanowires are not dissolvable in deionized water but can be dissolved by the metabolic materials released from bacteria, making them attractive for many biological applications.